PERBEDAAN HASIL KADAR FORMALIN PADA SAMPEL TAHU YANG DIRENDAM AIR HANGAT DAN AIR GARAM MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Indah Sari; Robiyatul Adawiyah; Nurhidayanti Nurhidayanti (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Formalin Examination is use to determine of presence or absence of harmful substances or preservatives in samples tested or examined on food, especially tofu. The Aim Of The Research: To determine the difference in the results of formaldehyde levels in tofu samples soaked in warm water and salt water using UV-Vis Spectrophotometry method. Research Method: The type of research used was a pure experiment, which was conducted at the Laboratory of Chemistry and Microbiology of Agricultural Products, Department of Agricultural Technology, Faculty of Agriculture, Unsri Palembang. The sample used was tofu and the number of careful samples was 18 tofu samples using the total sampling technique. The Result: Based on the results of examining the formalin content in tofu samples soaked in warm water for 15 minutes using the UV-Vis Spectrophotometry method with the A & E Visible Spectrophotometer yielded an average of 0.56 mg/L while the results of examining formalin levels in tofu samples soaked in salt water produces an average of 0.74 mg/L. Data analysis using the Independent Sample T-Test test obtained a significant value for the warm water treatment p = 0.395 and a significant value for the salt water treatment p = 0.397. Conclutions: There are differences in the results of formalin levels in tofu samples soaked in warm water and salt water using UV-Vis Spectrophotometry method.